Experimentos com os nematieidas D. D, E.D.B., C.B.P. e Vapam no combate aos nematódeos que parasitam a batatinha em São Paulo - Boock, O. J.; Lordello, Luiz Gonzaga E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
The writers report results on the application of four fumigants (D. D., E. D. B.-40, C. B. P. and Vapam) for control of root-knot and meadow nematodes attacking potato in beds filled with soil artificially inoculated. The data obtained were as follows: a) as reported by previous authors, potato is sensitive to C.B.P., the toxical effects of which disapearing only about 6 and half months after application. On the other hand, C.B.P. proved to have a significative residual nematicidal value, protecting the seeds from root-knot nematodes for a period of two years; b) D. D., E. D. B., and Vapam were effective for controling root-knot but with no residual value, having to be used prior to each planting; c) at the rates used, no nematicide was effective to control meadow nematodes; d) in the conditions of the experiments, all nematicides incited attacks bv Streptomyces scabies. Actually, in some cases scab did not affect any tuber from the check while the entire production from the treated beds was heavily desfigured. The writers assume that as the nematicides killed protozoa and too many bacteria-eating nematodes, they destroyed the biological equilibrium existing in the soil, thus allowing the S. scabies population to reach a high level.